For and against Organ Donation and Transplantation: Intricate Facilitators and Barriers in Organ Donation Perceived by German Nurses and Doctors - Niels Christian Hvidt; Beate Mayr; Piret Paal; Eckhard Frick; Anna Forsberg; Arndt Büssing (Journal of Transplantation)
Background. Significant facilitators and barriers to organ donation and transplantation remain in the general public and even in health professionals. Negative attitudes of HPs have been identified as the most significant barrier to actual ODT. The purpose of this paper was hence to investigate to what extent HPs (physicians and nurses) experience such facilitators and barriers in ODT and to what extent they are intercorrelated. We thus combined single causes to circumscribed factors of respective barriers and facilitators and analyzed them for differences regarding profession, gender, spiritual/religious self-categorization, and self-estimated knowledge of ODT and their mutual interaction. Methods. By the use of questionnaires we investigated intricate facilitators and barriers to organ donation experienced by HPs (n=175; 73% nurses, 27% physicians) in around ten wards at the University Hospital of Munich. Results. Our study confirms a general high agreement with the importance of ODT. Nevertheless, we identified both facilitators and barriers in the following fields: (1) knowledge of ODT and willingness to donate own organs, (2) ethical delicacies in ODT, (3) stressors to handle ODT in the hospital, and (4) individual beliefs and self-estimated religion/spirituality. Conclusion. Attention to the intricacy of stressors and barriers in HPs continues to be a high priority focus for the availability of donor organs.